A study on the Export of Small and Medium Enterprises in the Manufacturing - Azizi, Amir; Hosseini, Seyed Mehrshad Parvin; Lin, Lau Sow (2013)
Small and medium enterprises (SMEs) play a vital part in the economy of Malaysia as it form the largest business establishment in Malaysia. Most of the SMEs are predominantly owned and managed by local entrepreneurs. However, the contribution from SMEs manufacturing sector on value of gross domestic product (GDP) is relatively low as compare to other industries especially service industries.